Single-cell chromatin accessibility landscape of T cell-mediated rejection and BK polyomavirus-associated nephropathy after kidney transplantation - Jingyi Zhou; Hao Wu; Qin Zhou; Xudong Fu; Jianghua Chen (Renal Failure)
Both T cell-mediated rejection (TCMR) and BK polyomavirus-associated nephropathy (BKPyVAN) pose significant obstacles to successful kidney transplantation, emphasizing the importance of their accurate diagnosis for prompt medical intervention. Unfortunately, our current understanding of the molecular characteristics of these conditions is still limited, hampering the development of diagnosis strategies. In this study, we employed the single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) to unravel the chromatin landscape of kidney samples affected by either TCMR or BKPyVAN at the single-cell level. Our findings uncover distinct cell population dynamics and identify enriched pathways in the chromatin changes of TCMR and BKPyVAN samples, providing resources for further characterization of their molecular features. Furthermore, we analyzed the upstream transcriptional and epigenetic regulators modulating the chromatin landscape of each cell population in TCMR and BKPyVAN samples, shedding light on the identification of molecular mechanisms regulating TCMR and BKPyVAN.